MicroRNAs regulating macrophages infected with Leishmania L. (V.) Braziliensis isolated from different clinical forms of American tegumentary leishmaniasis - Lago, Tainã; Medina, Lilian; Lago, Jamile; Santana, Nadja; Cardoso, Thiago; Rocha, Alan; Leal-Calvo, Thyago; Carvalho, Edgar M.; Castellucci, Léa Cristina (Frontiers in Immunology, 2023)
Leishmania. There are still no vaccines and therapeutic options are limited, moving the constant need to comprehend fine mechanisms of its pathophysiology. An approach that has been explored in leishmaniasis is the participation of microRNAs (miRNAs), a class of small non-coding RNAs that act in most cases repressing gene expression. The miRNAs play a role in the complex and plastic interaction between host and pathogens, either as part of the host's immune response to neutralize infection or as a molecular strategy employed by the pathogen to modulate host pathways to its own benefit. Methods: Monocyte-derived macrophages from healthy subjects were infected with isolates of three clinical forms of L. braziliensis, cutaneous (CL), mucosal (ML) and disseminated (DL) leishmaniasis. We compared the expression of miRNAs that take part in the TLR/NFkB pathways. Correlations with parasite load as well as immune parameters were performed. Results: miRNAs 103a-3p, -21-3p, 125a-3p -155-5p, -146a-5p, -132-5p and -147a were differentially expressed in the metastatic ML and DL forms and there was a direct correlation between miRNAs -103a-3p, -21-3p, -155-5p, -146a-5p, -132-5p and -9-3p and parasite load with ML and DL isolates. We also found a correlation between the expression miR-21-3p and miR-146a-5p with the antiapoptotic gene BCL2 and the increasement of viable cells, whereas miR-147a was indirectly correlated with CXCL-9 levels. Conclusion: The expression of miRNAs is strongly correlated with the parasite load and and the inflammatory response, suggesting the participation of these molecules in the pathogenesis of the different clinical forms of L. braziliensis.